PELATIHAN BAHASA DAN SASTRA INDONESIA PARA GURU PONDOK PESANTREN DI KECAMATAN DIWEK, JOMBANG DI ERA DIGITAL - Thahirrah, Nadia Nur; Permata Raharjo, Resdianto; Supratno, Haris Supratno; Indriyanti, Aries Dwi; Kholifatu A.S, Arisni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Islamic boarding schools, as formal and non-formal educational institutions, play a strategic role in shaping the character of the nation's future generations. However, the teaching of Indonesian language and literature in Islamic boarding schools often faces obstacles because some teachers are not graduates of Indonesian language and literature education programs, resulting in a lack of mastery of linguistic rules and innovative teaching strategies. This Community Service (PKM) activity aims to improve teachers' competence in mastering Indonesian spelling, standard sentence writing based on digital technology, and creative and innovative teaching of Indonesian language and literature. The implementation methods include lectures, discussions, question and answer sessions, practice, mentoring, and evaluation. The results of the activity showed an increase in teachers' understanding and skills in teaching Indonesian language and literature, as indicated by their improved ability to write and teach using technology. The high enthusiasm of the participants demonstrated the success of the program, which is expected to continue in supporting the improvement of education quality in Islamic boarding schools.